2017
DOI: 10.1111/jvs.12584
|View full text |Cite
|
Sign up to set email alerts
|

Shift from facilitative to neutral interactions by the cushion plant Silene acaulis along a primary succession gradient

Abstract: Background:The stress-gradient hypothesis predicts a shift from facilitative to competitive plant interactions with decreasing abiotic stress. This has been supported by studies along elevation and temperature gradients, but also challenged by the hypothesis of a facilitation collapse at extremely harsh sites. Although facilitation is known to be important in primary succession, few studies have examined these hypotheses along primary succession gradients. Aim:To examine whether there is a relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 49 publications
2
28
1
Order By: Relevance
“…In fact, under relatively better environmental conditions (e.g., soil nutrient and water contents), species are less constrained by physical stresses and tend to compete for resources (Dohn et al., , and references therein). These findings are consistent with previous findings that in relatively benign conditions, where most species are tolerant of the local environment, species’ net interactions may be neutral or even competitive (Callaway et al., ; Kjaer et al., ; Michalet et al., ; Pugnaire & Luque, ), and hence support the stress‐gradient hypothesis (Bertness & Callaway, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, under relatively better environmental conditions (e.g., soil nutrient and water contents), species are less constrained by physical stresses and tend to compete for resources (Dohn et al., , and references therein). These findings are consistent with previous findings that in relatively benign conditions, where most species are tolerant of the local environment, species’ net interactions may be neutral or even competitive (Callaway et al., ; Kjaer et al., ; Michalet et al., ; Pugnaire & Luque, ), and hence support the stress‐gradient hypothesis (Bertness & Callaway, ).…”
Section: Discussionsupporting
confidence: 92%
“…Cushion and shrub species both modified the micro‐environments, but the magnitudes of their effects differed and varied along the environmental stress gradient (Table ; Figures ), suggesting that they do indeed act as ecosystem engineers (Jones et al., , ), thereby offering suitable micro‐sites for less tolerant species and leading to increases in species diversity (Anthelme et al., , ; Cavieres et al., ; Chen, Yang et al., ; Hupp et al., ; Kjaer, Olsen, & Klanderud, ; Yang et al., ). We found that cushions in the higher community support significantly higher species richness and abundance than equal surrounding areas (Figures ; Appendix ), indicating that cushions in such severe conditions can facilitate other species, possibly by offering suitable microhabitats.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies have suggested that species competition increases in later stages of succession only when VC approaches near maximum coverage of the foreland (Elven and Ryvarden 1975;Connell and Slatyer 1977;Jones and Henry 2003). Kjaer et al (2018) concluded specifically that species competition in later stages reflects the relative decrease in abiotic stress that dominates the early successional processes in proglacial environments. The observations presented herein are consistent with the conclusion that competition between bryophytes and vascular species (i.e., forbs and low shrubs) increased as VC increased on surfaces that are both older and at a greater distance from the ice front.…”
Section: Discussionmentioning
confidence: 99%
“…The cushion plant Silene has been found to host an increasing number of species at higher elevations (Antonsson, Björk, & Molau, ), while also demonstrating greatest facilitative effects on other species at the center of its elevational range (Bonanomi et al., ) as well as in abiotically stressful environments (Kjaer, Olsen, & Klanderud, ). We therefore expected cushion plants to first, host higher species diversity and richness compared to control areas, and second, maintain this higher diversity in areas where disturbance exerts negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…In undisturbed areas, species richness peaked at middle elevations instead of declining linearly with elevation. We suspect this is due to high levels of biotic competition at low elevations (Supporting Information Table A6 in Appendix S1) and high levels of abiotic stress at upper elevations, as well as The cushion plant Silene has been found to host an increasing number of species at higher elevations (Antonsson, Björk, & Molau, 2009), while also demonstrating greatest facilitative effects on other species at the center of its elevational range (Bonanomi et al, 2015) as well as in abiotically stressful environments (Kjaer, Olsen, & Klanderud, 2017). We therefore expected cushion plants to first, host higher species diversity and richness compared to control areas, and second, maintain this higher diversity in areas where disturbance exerts negative effects.…”
Section: Community Effects and Species Interactionsmentioning
confidence: 99%